Reinventando a tradição sobre "o lugar chegado" e "o lugar deixado" na migração contemporânea - Vieira, Márcia Rosane (Universidade do Vale do Rio dos Sinos, 2011)
This paper seeks to identify the identity/identification of young people from 12 to 21 years old, descendents of migrants from the southern states of Brazil (Parana, Santa Catarina and Rio Grande do Sul) to the north of Mato Grosso state, and that live in Sao Cristovao distric that are born in Sinop city. Thus, the locus is the outlook of youth migrant descendant of southerners to cultural heritage inherited from their parents, seeking in this way to unveil the games of belonging of these young people with respect to the South of the country, to the Mato Grosso or if there are simultaneous presence of the two cultures. The field research has made use of participant observation, semi-structured interviews and focus groups. The analysis runs through concepts such as identity, belonging, tradition, and translation.
Keywords: Juventude; Identidade; Pertencimento; Cultura; Youth; Identity; Belonging; Culture; ACCNPQ::Ciências Humanas::Sociologia